Offspring consume a more obesogenic diet than mothers in response to changing socioeconomic status and urbanization in Cebu, Philippines - Adair Linda; Kelles Anna (BMC, 2009)
Abstract Background Overweight increased among Filipino mothers and offspring from 1994 to 2005 however, a higher rate of increase among mothers resulted in a prevalence 4 times higher than that among offspring in 2005. Our aim was to explore the differential effects of changing income, assets, maternal education, and urbanicity on dietary behaviors of mothers and offspring that may affect overweight risk. Methods The study included a cohort of Filipino offspring and their mothers participating in the Cebu Longitudinal Health and Nutrition Survey at four time points from 1994 (n = 1,885 pairs) to 2005 (n = 1,349 pairs). The effect of socioeconomic factors and urbanicity, on dietary behaviors including energy adequacy, percent fat and carbohydrates were examined using longitudinal random-effects regression models. Results Mothers and offspring were consistently more likely to consume more calories relative to basal needs as well as a higher percent of calories from fat and a lower percent from carbohydrates with higher socioeconomic status and urbanization. Despite the substantially higher rates of overweight among mothers compared to offspring, offspring consumed a significantly more obesogenic diet than mothers experiencing the same increases in wealth and urbanicity. Conclusion Family-based interventions should be developed to counteract the shift towards a more obesogenic diet observed for both Filipino mothers and offspring.